Jual Beli Larva Black Soldier Fly Perspektif Maslahah Mursalah - Yuliah, Yuliah (At-Ta’awun: Jurnal Mu’amalah dan Hukum Islam, 2022)
This article is entitled Sale and Purchase of Black Soldier Fly Larvae from the Perspective of Maslahah Mursalah, which was conducted in Maron Village, Garung District, Wonosobo Regency. This research is included in field research which aims to answer two research questions, namely: 1. How is the Practice of Selling and Buying Black Soldier Fly Larvae in Maron Village, Garung District, Wonosobo Regency?. 2. How is Maslahah Mursalah Analysis of the Sale and Purchase of Black Soldier Fly Larvae in Maron Village, Garung District, Wonosobo Regency?. The results of the study indicate that the practice of buying and selling Black Soldier Fly Larvae from the perspective of maslahah mursalah has provided conditions for verifying which ones are considered maslahah and which are not. By classifying the types of maslahah according to their content. This is done in order to prevent humans from the speculative influence of humans who are only based on the interests of their ego in reasoning and considering a problem.